Pendidikan Toleransi Beragama pada Generasi Muda: Pengabdian di Desa Pakuhaji - Elmuna, Labib; Rifqi Fauzan, Yafie; Djun Nurain, Faisal; Fahri Ramdani, Muhammad (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
The initiative to develop religious tolerance among children through religious activities in Pakuhaji Village, West Bandung Regency, is a crucial step in addressing the potential religion conflicts and enhancing harmony in Indonesia's diversity. The community engagement method based on Participatory Action Research (PAR) is utilized to actively involve the community in the mentoring process. Through an inclusive and collaborative approach, the program successfully enhances the understanding of tolerance and religious harmony values among children in Pakuhaji Village. The mentoring outcomes demonstrate an improvement in understanding, practicing tolerance, and fostering a non-discriminatory attitude among children, with the hope of positively impacting the construction of a more harmonious and inclusive society.